A World Without Cows: Imagine Waking Up One Day to a New Reality. Issue 6 (November 2020) - Kanter, Mitch; Moore, Donald
Abstract : Dairy cows descended from animals that have been providing nourishment to humans for thousands of years. If cows no longer inhabited the earth, humans would lose a key source of high-quality protein and numerous other nutrients, as well as a source of revenue, livelihoods, and security for millions of people globally. Although cows are net greenhouse gas emitters, improved breeding and technology practices continue to generate more efficient cows that will continue to bring the dairy sector closer to becoming net zero emitters. In this article, intended and unintended consequences of waking up to a world without cows are explored.